TRANSFORMASI FILSAFAT MORAL DALAM PENDIDIKAN ISLAM - Angraini, Fera; Alting, Muhammad Guntur (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This article discusses the evolution and transformation of moral philosophy in the context of Islamic education. By tracing the historical course and development of moral conceptions in Islamic teachings, this article highlights significant changes in the approach to morality in Islamic education over time. From classical traditions to contemporary times, there has been a shift in thinking that influences the way morals are taught and understood within the framework of Islamic education. This research usedlibrary research, the method used is literature study. Literature research is research that examines different reference books, and the results of previous similar research help in obtaining a theoretical basis for the problem under study. In addition, focus is given to how universal values ​​in Islamic teachings such as justice, compassion, ethics and integrity are reinterpreted in the context of modern education, as well as how this influences the formation of the character and morals of future generations.By combining historical perspectives, philosophical analysis, and contemporary interpretation, this article aims to provide a deeper understanding of how moral philosophy in Islamic education has transformed over time and how it is relevant in facing moral challenges in the modern era